Donizetti's Lucia di Lammermoor - Cammarano, Salvatore, 1801-1852 (Opera Journeys, 2005)
A comprehensive guide to Donizetti's LUCIA DI LAMMERMOOR, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 25 music highlight examples.
Libretto by Salvatore Cammarano after Sir Walter Scott's novel The Bride of Lammermoor (1819).
Keywords: Donizetti, Gaetano, -- 1797-1848. -- Lucia di Lammermoor.; Lucia di Lammermoor (Donizetti, Gaetano); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos